Transdiagnostic Mechanisms in Autism Spectrum Disorder and Its Common Comorbidities: A review selected literature - Rouhafza, Mahsa; Askary, Reihaneh (Journal of Clinical Physiotherapy Research, 2025)
Introduction: Autism Spectrum Disorder (ASD) is a complex neurodevelopmental condition marked by persistent social-communicative deficits and repetitive behaviors. Its wide clinical heterogeneity and frequent psychiatric comorbidities, such as anxiety, obsessive-compulsive disorder (OCD), and attention-deficit/hyperactivity disorder (ADHD), challenge traditional diagnostic models. Given these complexities, the transdiagnostic approach has gained attention for targeting shared psychological and neurobiological mechanisms that transcend categorical diagnoses. The main purpose of this study was to review and synthesize existing articles on transdiagnostic mechanisms relevant to ASD and its common comorbidities. Method: This systematic review was conducted in accordance with PRISMA guidelines. A comprehensive literature search was performed in PubMed, Scopus, and PsycINFO for studies published from 2010 to 2024. Eligible studies examined emotion regulation, cognitive flexibility, or neural connectivity in individuals with ASD. Result: Seventeen studies met inclusion criteria. Emotion regulation deficits, cognitive inflexibility, and atypical neural connectivity emerged as prominent transdiagnostic factors. These processes were consistently linked to broader symptom profiles and psychiatric comorbidities. Conclusion: Identifying and addressing these shared mechanisms may improve intervention outcomes across diagnostic categories and support more personalized care in ASD. Integrating transdiagnostic insights into clinical practice could enhance functional outcomes and quality of life for individuals with ASD.